(untitled) (De Legibus - Law Journal, 2024)
The state of necessity consists of a situation in which the Administration is forced to act without the legality that, under normal conditions, binds it, in the name of urgent and unpostponable demands. It is not a question of acting against the law, but only of acting under the exceptional legality also provided for by the Code of Administrative Procedure. The Administration does not violate the law, it simply dispenses from it in order to resort to exceptional situations. Of course, acting in a state of necessity is also regulated by the Code of Administrative Procedure. Therefore, the adopted measures must be justified and proportional to the objectives pursued and any eventual injured parties are entitled to compensation for the damage caused.